If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(x + 11)(x + 9) = 1176 Reorder the terms: (4 + x)(x + 11)(x + 9) = 1176 Reorder the terms: (4 + x)(11 + x)(x + 9) = 1176 Reorder the terms: (4 + x)(11 + x)(9 + x) = 1176 Multiply (4 + x) * (11 + x) (4(11 + x) + x(11 + x))(9 + x) = 1176 ((11 * 4 + x * 4) + x(11 + x))(9 + x) = 1176 ((44 + 4x) + x(11 + x))(9 + x) = 1176 (44 + 4x + (11 * x + x * x))(9 + x) = 1176 (44 + 4x + (11x + x2))(9 + x) = 1176 Combine like terms: 4x + 11x = 15x (44 + 15x + x2)(9 + x) = 1176 Multiply (44 + 15x + x2) * (9 + x) (44(9 + x) + 15x * (9 + x) + x2(9 + x)) = 1176 ((9 * 44 + x * 44) + 15x * (9 + x) + x2(9 + x)) = 1176 ((396 + 44x) + 15x * (9 + x) + x2(9 + x)) = 1176 (396 + 44x + (9 * 15x + x * 15x) + x2(9 + x)) = 1176 (396 + 44x + (135x + 15x2) + x2(9 + x)) = 1176 (396 + 44x + 135x + 15x2 + (9 * x2 + x * x2)) = 1176 (396 + 44x + 135x + 15x2 + (9x2 + x3)) = 1176 Combine like terms: 44x + 135x = 179x (396 + 179x + 15x2 + 9x2 + x3) = 1176 Combine like terms: 15x2 + 9x2 = 24x2 (396 + 179x + 24x2 + x3) = 1176 Solving 396 + 179x + 24x2 + x3 = 1176 Solving for variable 'x'. Reorder the terms: 396 + -1176 + 179x + 24x2 + x3 = 1176 + -1176 Combine like terms: 396 + -1176 = -780 -780 + 179x + 24x2 + x3 = 1176 + -1176 Combine like terms: 1176 + -1176 = 0 -780 + 179x + 24x2 + x3 = 0 The solution to this equation could not be determined.
| 10u+7=8(-2m+5)-9 | | 3pqr+5pqr=0 | | 5/x=65/104 | | -9.2(x-1.75)=18.4 | | 10x+20x^2=100x-20x-3x | | 3x+120=126 | | 25+6x=40x | | =-1+5a-9(-2+5a) | | x+8-5x=-36 | | 11/3=22/x | | 1.2=3/5(x-3) | | 2x-3(x+4)=24 | | 8/x-2(-)3-3x/x | | 30+.05x=36.75 | | 5x-3-4x=7 | | 7x+1=141 | | 7x-3+3x=-63 | | 289=2x+7(-3x+25) | | 10x+3=2x+51 | | 8=12x | | 7X+30=9(X+2) | | 1/3b^-2 | | 2y+8=14x | | 5x+-1+2x=-29 | | 2x+(6-16)=-24 | | 12*4b=24 | | 8x+15=5x-2 | | 4/7=x/49 | | 12-b=3 | | (2/5)(2/5)(2/5) | | -43+32+4x=360 | | 4b-26=2 |